Pathology of Lymphoid Organs in Chlorpyriphos and T-2 Toxin Fed Broiler Chicken - Krishnamoorthy, P.; Vairamuthu, S.; Balachandran, C.; Muralimanohar, B. (International Journal of Poultry Science, 2006)
Forty-eight, newly hatched, unsexed broiler chicks were fed diets containing 45 mg/kg chlorpyriphos, an organophosphorus compound and 0.5 mg/kg T-2, a mycotoxin singly and in combination for 28 days from day of hatch to study the pathology of lymphoid organs. A system for scoring microscopic lesions was developed in bursa of Fabricius, caecal tonsil and spleen. Lesion scores for bursa ranged from 0 for normal, 2 for chlorpyriphos toxicosis and 4 for T-2 and chlorpyriphos+T-2 fed birds on 14th and 28th day of study. Less severe lesions occurred in caecal tonsils with score 1 in all the toxin fed birds. The lesion score for spleen ranged from 0 for normal to 3 for severely affected spleen in combined toxin fed birds on 14th and 28th day of trial. In T-2 fed group, thymus showed mild medullary lymphocytolysis on 14th day of trial. Harderian gland of all the toxin fed birds showed depletion of plasma cells and necrosis of the gland on 14th and 28th day of age. This lesion scoring system was useful in determining the severity of these two toxins singly and in combination on lymphoid organs in different age group of broilers. The present study revealed the individual and combined toxic effects of these toxins on the lymphoid organs and affecting the health status in broiler chicken.